Light-Induced Changes in Fatty Acid Profiles of Specific Lipid Classes in Several Freshwater Phytoplankton Species - Wacker, Alexander; Piepho, Maike; Harwood, John L.; Guschina, Irina A.; Arts, Michael T. (Frontiers in Plant Science, 2016)
We tested the influence of two light intensities [40 and 300 µmol PAR / (m² s)] on the fatty acid composition of three distinct lipid classes in four freshwater phytoplankton species. We chose species of different taxonomic classes in order to detect potentially similar reaction characteristics that might also be present in natural phytoplankton communities. From samples of the bacillariophyte Asterionella formosa, the chrysophyte Chromulina sp., the cryptophyte Cryptomonas ovata and the zygnematophyte Cosmarium botrytis we first separated glycolipids (monogalactosyldiacylglycerol, digalactosyldiacylglycerol, and sulfoquinovosyldiacylglycerol), phospholipids (phosphatidylcholine, phosphatidylethanol-amine, phosphatidylglycerol, phosphatidylinositol, and phosphatidylserine) as well as non-polar lipids (triacylglycerols), before analyzing the fatty acid composition of each lipid class. High variation in the fatty acid composition existed among different species. Individual fatty acid compositions differed in their reaction to changing light intensities in the four species. Although no generalizations could be made for species across taxonomic classes, individual species showed clear but small responses in their ecologically-relevant omega-3 and omega-6 polyunsaturated fatty acids in terms of proportions and of per carbon quotas. Knowledge on how lipids like fatty acids change with environmental or culture conditions is of great interest in ecological food web studies, aquaculture and biotechnology, since algal lipids are the most important sources of omega-3 long-chain polyunsaturated fatty acids for aquatic and terrestrial consumers, including humans.